2016
DOI: 10.1186/s12879-016-1344-2
|View full text |Cite
|
Sign up to set email alerts
|

Hepatitis C and not Hepatitis B virus is a risk factor for anti-tuberculosis drug induced liver injury

Abstract: BackgroundThe risk of anti-tuberculosis (TB) drug-induced liver injury (DILI) in patients with chronic viral hepatitis (CVH) is not clear. The aim of this study was to investigate incidence and risk factors associated with TB DILI in CVH and non-CVH patients.MethodsRetrospectively, a total of 128 CVH patients who received anti-TB medication from January 2005 to February 2014 were reviewed. Among these, 83 patients had hepatitis B virus (HBV), 41 patients had hepatitis C virus (HCV) and 4 patients were dual hep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
34
0
1

Year Published

2018
2018
2021
2021

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 54 publications
(36 citation statements)
references
References 27 publications
1
34
0
1
Order By: Relevance
“…Drugs such as antituberculosis drugs, methotrexate and antiretroviral drugs in HIV/AIDS-infected individuals have been implicated as triggering liver injury include particularly in the setting of underlying chronic liver disease due to hepatitis B or C [33][34][35][36][37]. Paradoxically CLD or cirrhosis is a risk factor for tuberculosis [38,39] and first-line anti-tuberculosis drugs have been consistently shown to increase the risk of hepatotoxicity, particularly in hepatitis B and C [40,41]. Although drugs have been listed as a precipitant factor in ACLF, data are scarce except from the APASL/AARC database.…”
Section: Defining the Acute Insultmentioning
confidence: 99%
“…Drugs such as antituberculosis drugs, methotrexate and antiretroviral drugs in HIV/AIDS-infected individuals have been implicated as triggering liver injury include particularly in the setting of underlying chronic liver disease due to hepatitis B or C [33][34][35][36][37]. Paradoxically CLD or cirrhosis is a risk factor for tuberculosis [38,39] and first-line anti-tuberculosis drugs have been consistently shown to increase the risk of hepatotoxicity, particularly in hepatitis B and C [40,41]. Although drugs have been listed as a precipitant factor in ACLF, data are scarce except from the APASL/AARC database.…”
Section: Defining the Acute Insultmentioning
confidence: 99%
“…The incidence of DILI was significantly higher in the HCV group (13/41 [31.7%], p<0.001) and the HBV + HCV group (3/4 [75.0%], p=0.002) than in the control group (25/251 [10.0%]). 56 Patients with TB receiving Isoniazid therapy showed a five-time higher increase in hepatic enzyme (ALT/AST) levels than the controls. This result indicates the presence of liver injury in TB patients.…”
Section: Discussionmentioning
confidence: 96%
“…110 A recent retrospective study involving 379 (including 128 patients with chronic viral hepatitis) receiving anti-TBC therapy found that HCV on its own or in combination with HBV was associated with increased incidence of DILI. 111 HIV infection has also been shown to increase the risk of anti-TBC DILI by 4-fold and coinfection with HCV increased this risk by 14-fold. 112 In a large cohort of DILI, 10% had pre-existing liver disease, mainly chronic hepatitis C or raised liver enzymes; azithromycin was the implicated agent in a higher proportion of patients with pre-existing liver disease (6.7%) compared to those without liver disease (1.5%).…”
Section: Statementmentioning
confidence: 99%